Optimization Of Packing Material Inventalory Using ABC Analysis, Forecasting Methods, and Economic Order Quantity - Pamolango, Marchello; Dewantoro, Albertus Daru (Tibuana, 2026)
Inventory management of packing materials in the flexible packaging industry often faces high investment value, inaccurate demand planning, and inefficient ordering quantities. This study aims to determine material priorities and optimal order quantities to minimize total inventory costs through an integrated approach. The methodology combines ABC Analysis for material classification, forecasting methods (Simple Average, Moving Average, Weighted Moving Average, and Single Exponential Smoothing) to predict demand, and Economic Order Quantity (EOQ) to determine optimal purchasing quantities. The results show that PLY material is categorized as class A with an investment contribution of 64.53%. Among forecasting methods, the 3-period Weighted Moving Average provides the best accuracy with the lowest MAPE value of 15.81%. EOQ calculations indicate optimal order quantities of 15,849 units for Plywood Multi 0280x0280x09 dia 77 and corresponding optimal quantities for other PLY materials. The integration of ABC, forecasting, and EOQ improves inventory efficiency and supports more reliable production planning.